Lube Oil Cooler Performance Analysis Before and After Maintenance Outage at PLTGU - Saputra, Andrian Nurul; Puspawan, Angky; Supardi, Nurul Iman (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2021)
This work has been done in one of the gas and steam power generating units in the Southern Sumatra. Lube oil cooler is a cross flow compact heat exchanger that functions to release the heat carried by lubricating oil flowing through the shell side to the tube side with water cooling fluid where each liquid is separated in the lube oil cooler the ratio of the heat transfer coefficient on the shell and pipe sides tube and the effectiveness of heat transfer that occurs. It can be concluded that before maintenance outage the logmean temperature difference value (LMTD) was 15.48 oC while after maintenance outage the LMTD value decreased to 10.52 oC. The effectiveness value before maintenance outage was 50.62%, whereas after maintenance outage was carried out the average value increased by 59.61%. So that a good performance is in the condition after the maintenance outage.